Punction biopsy for diagnostics of neoplasms in thoracic and lumbar spine - Popov, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The final stage of spine neoplasm diagnostics is histological examination. In order to obtain the tissue from neoplasm punction biopsy is used. Objective: to assess the efficacy of punctional biopsy with further pathohistological examination in patients with neoplasm in thoracic and lumbar spine. Methods: we analyzed 259 case histories of patients with pathological spine changes. Results: punction biopsy was made in 238 patients (89 %). In 30 (11 %) patients it was no effective because of the large amount of obtained material, in 27 (10 %) pathohistological diagnosis was not established. Pepeated biopsy was made in these cases. As a result at primary and secondary biopsies the diagnosis was confirmed in 95.5 %. Conclusions: punctional biopsy with pathohystological examination is integral part of diagnostic process at spine neoplasm. It allows to obtain enough material for studying (inspite of the dense of tissues) to decrease the risks of contamination of surrounded tissues. Such minimalinvasive method gives possibility to use it in patients with comorbidities. Most of primary spine cancer is represented by myeloma and malignant lymphoma. Episodic were cases of hondrosarcoma, osteosarcoma and fibrosarcoma, when the lesion was spread on one or two vertebrae. Most frequent non malignant lesions were haemangioma and eosinophilic granuloma. Metastatic disease were revealed in 74 (28 %) of patients and often appeared in cases of low grade cancer and adenocarcinoma.